Clinical characteristics and genetic features of 35 cases of adverse reactions to Bacillus Calmette-Guérin vaccine in children - Chen, Houyu; Yang, Xiaotao; Huang, Yi; Jiao, Feng; Bai, Houxi; Zhu, Ying; Cui, Penghao; Jin, Haifeng; Guo, Yan; Wang, Yanchun; Luo, Yonghan (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThis study aimed to analyze the clinical characteristics and genetic features of children with adverse reactions to the Bacillus Calmette-Guérin (BCG) vaccine. The goal was to improve understanding of this condition, provide insights into early diagnosis and intervention, and support stratified management.MethodsClinical data of 35 children hospitalized at Kunming Children’s Hospital between January 2014 and June 2024 with complete records and diagnosed with BCG vaccine adverse reactions were collected. Cases were classified into two groups: disseminated BCG disease (BCG-D) and BCG-itis. Children with primary immunodeficiency (PID) were further divided into severe combined immunodeficiency (SCID) and non-SCID groups. Clinical characteristics, immunological profiles, genetic backgrounds, and outcomes were compared between the groups.ResultsAmong the 35 cases, 25 were male, and 10 were female, with a median age of onset of 2 months (1–4 months). Eight cases (22.9%) were diagnosed with BCG-D, while 27 cases (77.1%) were classified as BCG-itis. Sixteen cases (45.7%) were confirmed to have PID, including SCID (7 cases, 20.0%), chronic granulomatous disease (6 cases, 17.1%), Mendelian susceptibility to mycobacterial disease (2 cases, 5.7%), and fas associated via death domain (FADD) gene mutation (1 case, 2.6%). Compared to the BCG-itis group, the BCG-D group exhibited significantly higher rates of fever, hepatosplenomegaly, elevated white blood cell counts, neutrophil counts, and C-reactive protein (CRP) levels, along with lower red blood cell counts and hemoglobin levels (p<0.05). Similarly, the SCID group showed significantly lower age, lymphocyte counts, IgM levels, CD3, CD4, and CD8 cell ratios, but higher CD19 cell ratios and mortality rates compared to the non-SCID group (p<0.05). Twenty-seven (77.1%) cases were discharged after improvement, and eight children (22.9%) succumbed to the condition, including six with SCID gene mutations (representing 85.7% of the total SCID cases), one with an interleukin 12 receptor subunit beta 1(IL12RB1) mutation, and one who was not genetically tested but diagnosed with disseminated BCG disease.ConclusionsIn children presenting with adverse reactions to the BCG vaccine, the presence of fever, hepatosplenomegaly, elevated neutrophil levels, and CRP should prompt evaluation for disseminated BCG disease and assessment of immunological status. Early identification of underlying PID, particularly SCID, is crucial, given the high mortality and poor prognosis associated with the condition, necessitating timely interventions.